Influence of mortar water content and workability on the mechanical behaviour of lime mortar masonry - COSTIGAN, ADRIAN; PAVIA, SARA (My University, 2010)
Water content affects mortar properties and the quality of the resultant masonry, however, it is often subjectively determined by the mason by assessing workability. This lack of explicit methodology and data, can lead to lack of mortar consistency and field performance, adversely affecting full uptake of lime mortars into mainstream technology. The aim of this research is to assist develop consistent lime mortars of high quality, that would improve the strength and durability of masonry. To this aim, the paper investigates the compressive, flexural and bond strength of clay brick masonry bound with natural hydraulic lime mortar (NHL2), at variable water contents delivering different workabilities. The results evidenced that increasing the water content by 1% yields a 5mm increase in initial flow (from 165 to 170mm). It was found that this water increment significantly increases the mortar?s compressive strength simultaneously reducing its flexural strength, but it does not increase stiffness under compression. It was also evidenced that the 1% water increment significantly enhances the masonry?s compressive, bond and flexural strengths. From these, it was concluded that mixing NHL2 mortars to produce a 170mm initial flow will result in a consistently adequate strength and mechanical behaviour for mortar and masonry.
BCRI Bridge Infrastructure Concrete Research Ireland
PUBLISHED
University College Cork
Keywords: Construction engineering; compressive and flexural strength; flexural bond strength; lime mortar masonry